Paradox of rice seed system in India - Hossain, S.K. Mosharaf; Nayak, Swati (Grassroots Institute, 2020)
Importance of rice in agrarian economy of India is enormous. In order to meet demand of this staple crop for increasing population, productivity enhancement is a key research and development agenda. Improving seed replacement rate is widely held as a critical area to boost rice productivity in the country. This study based on secondary data revealed merely sowing quality seeds may not result in desired level of yield increase unless quality seeds of a good and appropriate variety is sown. Punjab, with its 38% SRR, registers 3.97 ton per ha yield whereas it is just 1.51 ton per ha in Chattisgarh where SRR is 44%. There are many varieties, quite older than stipulated 10 years, that are largely indented and grown due to lack of substitutes and poor varietal awareness. Because of this slow varietal awareness and replacement, rice yield still stagnates despite seeds are of assured quality. This shows varietal replacement rate is as important as seed replacement rate. The available studies also indicate that current seed system further needs to rationalize variety selection, production and multiplication of breeder seeds for ensuring seed security of farmers and this should be supplemented by measures taken to promote varietal promotion and replacement, quality seed production interventions at farmers’ level, and decentralized seed production system.